Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1073/pnas.91.5.1858
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin gene mutations in human gastric carcinomacell lines.

Abstract: Reduced expression of E-cadherin has been regarded as one of the main molecular events involved in dysfunction of the cell-cell adhesion system, triggering cancer invasion and metastasis. However, even with a sufficient amount of E-cadherin, cell-cell adhesion is sometimes lost in "diffusely invasive" human carcinomas. Ten human cancer cell lines, showing growth characterized morphologically by loose cell-cell adhesion, were analyzed for possible structural abnormalities of their expressed E-cadherin. Four of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
176
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(184 citation statements)
references
References 33 publications
6
176
0
2
Order By: Relevance
“…10 Somatic E-cadherin mutations that impair the adhesive function of the protein have been described in diffuse type gastric carcinomas. [11][12][13][14][15][16] The predominant type of mutations in gastric cancer were splice-site mutations and in-frame deletions and most of the mutations were located in exons 8 or 9. 16,17 Although a number of in vitro investigations have established the significance of Rac1, IQGAP1 and Tiam1 as regulators of E-cadherin-mediated cell adhesion, little is known about the relevance of these markers in gastric cancer.…”
mentioning
confidence: 99%
“…10 Somatic E-cadherin mutations that impair the adhesive function of the protein have been described in diffuse type gastric carcinomas. [11][12][13][14][15][16] The predominant type of mutations in gastric cancer were splice-site mutations and in-frame deletions and most of the mutations were located in exons 8 or 9. 16,17 Although a number of in vitro investigations have established the significance of Rac1, IQGAP1 and Tiam1 as regulators of E-cadherin-mediated cell adhesion, little is known about the relevance of these markers in gastric cancer.…”
mentioning
confidence: 99%
“…8 Abnormal E-cad expressions, including cytoplasmic translocation, heterogeneous, and/or absence of expression have been reported in aggressive carcinomas of the esophagus, stomach, and breast. 9,10 Mutation of the E-cad gene and loss of heterozygosity (LOH) of this gene have also been detected in cell lines of gastric [11][12][13][14][15] and breast carcinomas. 16 Previous studies of this gene in adenoid cystic carcinoma have reported a reduced expression of E-cad protein in high grade and aggressive tumors.…”
mentioning
confidence: 99%
“…The mechanisms that lead to the loss of E-cadherin expression in the cell membrane are still unclear. The disruption of cell-to-cell adhesion might be mediated by several factors, such as digestion by proteases (Lochter et al, 1997;Steinhusen et al, 2001), transcriptional repression (Batlle et al, 2000;Cano et al, 2000;Yap et al, 2007), endocytosis (Fujita et al, 2002), mutations in the E-cadherin gene (Oda et al, 1994;Saito et al, 2001) and methylation of E-cadherin promoter (Yoshiura et al, 1995).…”
Section: Discussionmentioning
confidence: 99%